Implementation of Self-regulated Learning Strategies in Nepal (Research Journal, 2025)
This article is a result of implementing self-regulated learning strategies in Nepal considering its basic features like mediation, ZPD, agency, autonomy, principled pragmatism, metacognitive strategies and modern technologies. Necessary data were collected from a real classroom setting maintaining a portfolio of students who studied at Mahendra Ratna Multiple Campus, Ilam. This article attempts to share the classroom experience of putting the SRL strategies into practice among the bachelor’s fourth-year students who studied the research methodology course which is both theoretical and practical in nature. More specifically, the practical activities require self-regulated learning strategies to prepare a research report based on the basic components of research given in the course. The students should work hard from the very beginning of the session to the end to shape and reshape the research topic and prepare the final research report. This study shows that twenty-one students who were involved more sincerely while doing those activities effectively implementing the features of SRL achieved satisfactory results.